Linking the representation levels to a physical separation and purification method in chemistry: Understanding of distillation experiment - Nalan Akkuzu Güven; Melis Arzu Uyulgan (Journal of Pedagogical Research, 2021)
The present investigation aims to analyze the knowledge levels and chemical representation levels of pre-service primary school teachers (PPSTs) on the experiment of distillation. For this purpose, the cross-sectional survey technique, one of the quantitative research designs was employed. The study was carried out at a Faculty of Education in the Aegean Region of Turkey with 79 freshman pre-service teachers enrolled in the Department of Primary Education. This group is of particular interest as they are the last class who had taken the General Chemistry course since this course was removed from the curriculum in 2018. A Distillation Experiment Worksheet (DEW), which consisted of 9 open-ended questions involving the macroscopic, sub-microscopic, and symbolic representations was used as data collection instrument in the study. The worksheets were analyzed with the document analysis method according to the categories created within the scope of the chemical representation levels, and these categories were established in line with direct statements of the PPSTs. Results indicated that PPSTs confused the heterogeneous and homogeneous mixtures, physical properties such as volatility and density, and they were unable to differentiate between boiling and evaporation. The most crucial result of the study was that the PPSTs had difficulties in establishing a relationship between macroscopic and sub-microscopic representations. For this reason, they could not demonstrate the interactions between solvent and solute molecules at the sub-microscopic level during molecular dissolution and they could not predict how the intermolecular interaction changes during the condensation and the distance between the particles. Based on the results of this analysis, our study provides several recommendations for lecturers in the last part of this paper.